(untitled) (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. In modern conditions of development of national economy educational-scientific and practical components are the most actual in formation of competitiveness of the enterprises. It is the synergistic combination of the above components that helps to increase the level of personnel management, its labor potential, ensuring the efficiency of work. Goal of the article is to theoretically substantiate and develop practical recommendations for areas of synergistic combination of education, practice and science in the context of ensuring the effectiveness of work. Methods. The article uses a monographic method, analysis, method of generalization of scientific approaches, method of sociological survey. Results. The article provides a theoretical analysis of educational and scientific factors to ensure the effectiveness of labor activity. A sociological survey of students on the impact of educational factors on the effectiveness of practical activities of graduates. It is determined that a high share of the practical component in educational programs contributes to the acquisition of skills, development of professional and personal potential. The directions of ensuring the efficiency of labor activity are developed by taking into account the organization of payment, labor motivation, improvement of labor rationing, increase of creative nature of labor and responsibility of employees for labor results. Conclusions. The study allows to generalize scientific approaches to the synergistic combination of education, science and practice in the context of ensuring the effectiveness of work.